2005
DOI: 10.1038/nmat1394
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic, atomic structure and chemistry changes induced by Ca-doping of low-angle YBa2Cu3O7–δ grain boundaries

Abstract: Practical high-temperature superconductors must be textured to minimize the reduction of the critical current density J(gb) at misoriented grain boundaries. Partial substitution of Ca for Y in YBa(2)Cu(3)O(7-delta) has shown significant improvement in J(gb) but the mechanisms are still not well understood. Here we report atomic-scale, structural and analytical electron microscopy combined with transport measurements on 7 degrees [001]-tilt Y(0.7)Ca(0.3)Ba(2)Cu(3)O(7-delta) and YBa(2)Cu(3)O(7-delta) grain bound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 32 publications
4
76
0
Order By: Relevance
“…So far as the possibility of intrinsic granularity is concerned, one important factor is likely to be the low carrier density of ~10 21 cm -3 [4] which is very similar to that found in the cuprates and which produces an intrinsic weak-link behavior at high-angle cuprate grain boundaries [28,29]. However, many additional specific features of the cuprates, including their sensitivity to local oxygen concentration, proximity of the superconducting state to the Mott metal-insulator transition, and cation disorder [30], also play important roles in depressing the superconducting order parameter at grain boundaries. Explicit understanding of the oxypnictides awaits single grain boundary studies that are not yet possible, so for now we restrict our discussion to extrinsic factors that may be playing a role in the behavior of these two Nd and Sm samples, that actually show much better global current flow than the La oxypnictide sample first studied [12].…”
Section: Discussionmentioning
confidence: 99%
“…So far as the possibility of intrinsic granularity is concerned, one important factor is likely to be the low carrier density of ~10 21 cm -3 [4] which is very similar to that found in the cuprates and which produces an intrinsic weak-link behavior at high-angle cuprate grain boundaries [28,29]. However, many additional specific features of the cuprates, including their sensitivity to local oxygen concentration, proximity of the superconducting state to the Mott metal-insulator transition, and cation disorder [30], also play important roles in depressing the superconducting order parameter at grain boundaries. Explicit understanding of the oxypnictides awaits single grain boundary studies that are not yet possible, so for now we restrict our discussion to extrinsic factors that may be playing a role in the behavior of these two Nd and Sm samples, that actually show much better global current flow than the La oxypnictide sample first studied [12].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Depression of multiband superconductivity at GBs in pnictides could result from strong interband scattering by imperfect GB structural units in the chain of GB dislocation cores or by strain-or charge-driven Cottrell atmospheres of segregated impurities at the GB. 22,23 Strong antiferromagnetic correlations in the Fe-As planes and GB impurity segregations may also induce local magnetic nanostructures, which would also contribute to the weak link behavior 5 of GBs in pnictides. Given the strong coupling of the superconducting order parameters in different bands, 24 pairbreaking magnetic and nonmagnetic scattering at the GB may play a much greater role in the order parameter suppression at GBs in 122 than in the two-band superconductor MgB 2 in which weak interband coupling and interband impurity scattering are consistent with the lack of weak link behavior of GBs.…”
mentioning
confidence: 99%
“…As described in the introduction, one of the major motivations to study (Yb 1-x Ca x )BCO was to explore the effects of a stronger Ca segregation to GBs predicted by the strain-charge model [7]. This model successfully described the observed non-uniform Ca distribution along and across GBs in Ca-doped YBCO.…”
Section: Gbmentioning
confidence: 99%
“…The strength and orientation of the magnetic field have a significant effect on GB transparency too. A number of studies [5][6][7] found that J c of the GB and the grain converged with increasing field. The field at which J c GB converged with J c grain was found to increase with GB misorientation angle θ. Diaz et al [8] found that J c GB peaks in an angular-dependence study of J c GB , when the magnetic field was aligned with the GB dislocations.…”
Section: Introductionmentioning
confidence: 99%